Small Body, Large Chromosomes: Centric Fusions Shaped the Karyotype of the Amazonian Miniature Fish Nannostomus anduzei (Characiformes, Lebiasinidae) - de Moraes, Renata Luiza Rosa; Sassi, Francisco de Menezes Cavalcante; Marinho, Manoela Maria Ferreira; Ráb, Petr; Porto, Jorge Ivan Rebelo; Feldberg, Eliana; Cioffi, Marcelo de Bello (Genes, 2023)
Miniature refers to species with extraordinarily small adult body size when adult and can be found within all major metazoan groups. It is considered that miniature species have experienced severe alteration of numerous morphological traits during evolution. For a variety of reasons, including severe labor concerns during collecting, chromosomal acquisition, and taxonomic issues, miniature fishes are neglected and understudied. Since some available studies indicate possible relationship between diploid chromosome number (2n) and body size in fishes, we aimed to study one of the smallest Neotropical fish Nannostomus anduzei (Teleostei, Characiformes, Lebiasinidae), using both conventional (Giemsa staining, C-banding) and molecular cytogenetic methods (FISH mapping of rDNAs, microsatellites, and telomeric sequences). Our research revealed that N. anduzei possesses one of the lowest diploid chromosome numbers (2n = 22) among teleost fishes, and its karyotype is entirely composed of large metacentric chromosomes. All chromosomes, except for pair number 11, showed an 18S rDNA signal in the pericentromeric region. 5S rDNA signals were detected in the pericentromeric regions of chromosome pair number 1 and 6, displaying synteny to 18S rDNA signals. Interstitial telomeric sites (ITS) were identified in the centromeric region of pairs 6 and 8, indicating that centric fusions played a significant role in karyotype evolution of studied species. Our study provides further evidence supporting the trend of diploid chromosome number reduction along with miniaturization of adult body size in fishes.
Keywords: karyotyp; 2n reduction; karyotypizace; Characiformes; ribozomální DNA; karyotype; Telomere; Animals; Karyotype; DNA, Ribosomal; zvířata; neotropical fishes; Karyotyping; telomery; chromosomal rearrangements